The impact of rankings on the quality and accessibility of higher education (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the impact of ranking systems on the quality and accessibility of higher education. Rankings are emphasized as a tool for enhancing the competitiveness of universities and serving as a benchmark for consumers of educational services. Current trends in national and international rankings are analyzed, highlighting their key indicators and assessment methods. Special attention is given to the influence of rankings on the strategic development of higher education institutions in the Kyrgyz Republic, including the improvement of educational programs, increased institutional efficiency, and integration into the global educational space. Based on systems analysis and modeling methods, an approach to the development of an institutional and program-based ranking system is proposed, ensuring objectivity and transparency of evaluation criteria. The review and analysis of works on the issue of ranking in university education is given. The methodology of the rating system of educational activities of universities has been developed and presented.
Keywords: rankings, higher education, education quality, education accessibility, university competitiveness, integration, education policy, methodology, systems analysis, business process